2011
DOI: 10.3357/asem.3050.2011
|View full text |Cite
|
Sign up to set email alerts
|

Helicopter Crashes Related to Oil and Gas Operations in the Gulf of Mexico

Abstract: Mechanical failure, non-activation of flotation, and pilot error are major problems to be addressed if crashes and deaths in this lethal environment are to be reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…The reports were examined for information related to the number of individuals onboard (aircrew and passengers), time of day, cause of accident, warning time, position at the surface, and whether the helicopter inverted immediately after impact. Based on previous research, it was expected that the majority of the reports would be missing detailed information regarding survival specific factors (Baker et al, 2011;Brooks et al, 2008;Taber and McCabe, 2006).…”
Section: Methodsmentioning
confidence: 98%
“…The reports were examined for information related to the number of individuals onboard (aircrew and passengers), time of day, cause of accident, warning time, position at the surface, and whether the helicopter inverted immediately after impact. Based on previous research, it was expected that the majority of the reports would be missing detailed information regarding survival specific factors (Baker et al, 2011;Brooks et al, 2008;Taber and McCabe, 2006).…”
Section: Methodsmentioning
confidence: 98%
“…dust) (Hart, 1988). Baker et al (2011) found that bad weather was the second most common precipitating factor (after mechanical failure) for fatal and nonfatal crashes in their analysis of 178 Gulf of Mexico helicopters accidents. Furthermore, the bad weather accidents resulted in the largest number of deaths (40 percent of all deaths).…”
Section: Rotary Wing Aviationmentioning
confidence: 96%
“…The operational benefits afforded to helicopters and the associated contexts of use have driven an increased demand for their use in DVE in a civilian setting (Baker et al, 2011;BHA, 2014). Furthermore, the ability to fly at low altitudes makes rotary wing aircrafts more susceptible to issues arising from low visibility for greater proportions of flight, not just critical phases.…”
Section: Rotary Wing Aviationmentioning
confidence: 99%
“…In 2013, an accident in the UK saw the death of an experienced rotary-wing pilot and a civilian after a helicopter collided with a crane jib, whilst flying through dense fog, in central London (AAIB 2013). Erroneous pilot decision making including continued visual flight into instrument conditions and neglecting to check weather conditions was a contributing factor in 40% of rotary-wing accidents supporting gas operations in the Gulf of Mexico between 1983 and 2009 (Baker et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to increasing flight safety, the potential economic benefits of reducing flight delays and cancellations drive the development of new technologies to increase operational capacity in degraded visual environments for civil aviation (Prinzel Iii et al 2004;Hemm 2000;Cahill et al 2016). The operational benefits of rotary-wing aircrafts include the capacity to fly at low altitude, take-off and land vertically, and hover with zero ground speed (Baker et al 2011;Swail and Jennings 1999;Grissom et al 2006;Alppay and Bayazit 2015). The ability to fly to unimproved landing sites, without aviationrelated ground infrastructure, extends the potential use of rotary-wing aircraft for public transportation (BHA 2014) and, however, also leads to a greater exposure to potential risks, especially when operating in degraded visual conditions.…”
Section: Introductionmentioning
confidence: 99%